A Descriptive Study to Assess the Prevalence of Factor Related to CKD among Patients with CKD Admitted at NMCH Jamuhar, Rohtas, Bihar, India - K. Latha; Dinesh Kumawat; Anish Kumar; Chandan Kumar Purbey; Rohit Kumar; Beauty Kumari; Kajal Kumari (Journal of Medicine and Health Research, 2026)
Background: Chronic Kidney Disease (CKD) is a progressive and irreversible disorder that has emerged as a major global public health challenge because of its increasing prevalence, high morbidity and mortality, and economic burden. Diabetes mellitus, hypertension, obesity, smoking, cardiovascular disease, and prolonged use of nephrotoxic drugs are recognised as major contributors to CKD progression. Early identification of these factors is essential for reducing complications and improving patient outcomes. Objectives: To assess the prevalence of factors associated with Chronic Kidney Disease among patients admitted to Narayan Medical College and Hospital (NMCH), Jamuhar, Rohtas, Bihar, and determine their association with selected socio-demographic variables. Methods: A quantitative, descriptive cross-sectional study was conducted among 60 patients diagnosed with CKD who were admitted to the nephrology and medical wards of NMCH, Bihar. Participants were selected using a non-probability convenience sampling technique. Data were collected using a structured socio-demographic questionnaire and a checklist assessing CKD-related factors. Descriptive statistics (frequency and percentage) and inferential statistics (chi-square test) were performed using IBM SPSS version 26.0. A p-value < 0.05 was considered statistically significant. Results: Hypertension was the most prevalent associated factor (75.0%), followed by diabetes mellitus (63.3%), smoking (40.0%), alcohol consumption (33.3%), obesity (31.7%), cardiovascular disease (30.0%), long-term NSAID use (28.3%), kidney stones (25.0%), recurrent urinary tract infection (23.3%), and family history of CKD (20.0%). Significant associations were observed between CKD-related factors and age (p = 0.008), gender (p = 0.031), educational status (p = 0.030), residence (p = 0.017), and duration of CKD (p = 0.031). Conclusion: Hypertension and diabetes mellitus remain the predominant factors associated with CKD among hospitalised patients. Early screening, lifestyle modification, patient education, and effective management of modifiable risk factors should be prioritised to delay disease progression and improve health outcomes.